2016
DOI: 10.1094/phyto-04-14-0099-r
|View full text |Cite
|
Sign up to set email alerts
|

Population Structure of Phytophthora nicotianae Reveals Host-Specific Lineages on Brinjal, Ridge Gourd, and Tomato in South India

Abstract: Severe outbreaks of Phytophthora fruit rot on brinjal, ridge gourd, and tomato have been observed since 2011 in Andhra Pradesh, Karnataka, Telangana, and Tamil Nadu states of India. Therefore, 76 Phytophthora nicotianae isolates, recovered from brinjal (17), ridge gourd (40), and tomato (19) from different localities in these states during the June to December cropping season of 2012 and 2013, were characterized based on phenotypic and genotypic analyses and aggressiveness on brinjal, tomato, and ridge gourd. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…isolates suggest pathogen's adaptability and efficiency in infecting its native hosts such as durian and cacao. The result was similar to the findings of Chowdappa et al (2016) where different genotypes of P. nicotianae from brinjal, ridge gourd and tomato formed a hostspecific groupings of the isolates in the phylogenetic tress generated using the combined dataset of three mitochondrial regions. Wyand and Brown (2003) also observed the grouping of isolates according to their host in the phylogenetic analysis of different formae speciales of the Blumeria graminis using rDNA ITS and βtubulin (β-tub) genes, which was further confirmed through AFLP analysis (Borah et al, 2018).…”
Section: Discussionsupporting
confidence: 87%
“…isolates suggest pathogen's adaptability and efficiency in infecting its native hosts such as durian and cacao. The result was similar to the findings of Chowdappa et al (2016) where different genotypes of P. nicotianae from brinjal, ridge gourd and tomato formed a hostspecific groupings of the isolates in the phylogenetic tress generated using the combined dataset of three mitochondrial regions. Wyand and Brown (2003) also observed the grouping of isolates according to their host in the phylogenetic analysis of different formae speciales of the Blumeria graminis using rDNA ITS and βtubulin (β-tub) genes, which was further confirmed through AFLP analysis (Borah et al, 2018).…”
Section: Discussionsupporting
confidence: 87%
“…VOCs are substances with a low molecular weight (<300 Da), high vapor pressure (≥0.01 kPa at 20 • C), and low water solubility (Pagans et al, 2006;Delgado et al, 2021). The VOCs synthesized by microbes contains a variety of compounds such as esters, alcohols and aromatic compounds (de Boer et al, 2019). The present study revealed that the volatiles produced by H. uvarum MP1861 contained ethyl acetate, isopentyl alcohol (1-butanol, 3-methyl-, acetate), and phenylethyl alcohol.…”
Section: Discussionmentioning
confidence: 64%
“…Phytophthora nicotianae , first isolated from tobacco, is an important pathogen because it causes severe damage to a particularly large number of host plants (Panabieres et al, 2016 ). More than 255 plant species can be infected by P. nicotianae , including tomato, tobacco, potato, citrus, and eggplant (Chowdappa et al, 2016 ; Panabieres et al, 2016 ). At present, the application of fungicides, such as formanyl, hymexazol, and dimethomorph, is the main method to prevent the occurrence of plant diseases caused by P. nicotianae (Han et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…-P. nicotianae (Sullivan et al, 2010). Host specific lineages have been reported for P. nicotianae, evidence suggests that isolates may be more aggressive in their host of origin than in other plant hosts and clonality prevails in pathogen populations suggesting asexual dispersion (Mammella et al, 2013;Biasi et al, 2016;Chowdappa et al, 2016). Lamour et al (2003) evaluated isolates from different geographic areas and observed a similar compatibility between them and the host, a characteristic maybe due to asexual reproduction of P. nicotianae.…”
Section: Discussionmentioning
confidence: 92%